Transparent nanofiber textiles with intercalated ZnO@graphene QD LEDs for wearable electronics - Lee, Kyu Seung; Shim, Jaeho; Park, Mira; Kim, Hak Yong; Son, Dong Ick (ELSEVIER SCI LTD, 2017)
Transparent human hair-based textiles, which are founded on a natural resource, have been fabricated by an electrospinning technique. Transparent human hair-based textiles are very useful for transparent wearable electronics because they have unique optical properties in the visible light region such as transparency of over similar to 85%. In order to apply wearable electronic devices with transparent textiles, we fabricated sandwich structures with transparent flexible light emitting diodes (LEDs) embedded in transparent nanofiber textile utilizing ZnO@graphene quantum dots (ZGQDs) and demonstrated the fabrication process and characterization of ZGQD LEDs with textiles. We believe that these results will inspire new methods in wearable electronics and raise the hope of achieving even higher efficiencies by means of development and control of transparent textile ordering. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: FABRICATION